2016
DOI: 10.1097/md.0000000000003533
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency Strongly Predicts Adverse Medical Outcome Across Different Medical Inpatient Populations

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 59 publications
1
4
0
2
Order By: Relevance
“…These associations tempt us to believe that improvement in nutritional status by the use of nutritional interventions also leads to improvements in patient outcomes. However, similar findings have been reported for nutritional factors, such as vitamin D, where associations suggested harmful effects, but intervention research failed to find benefit [ 15 , 16 ]. Still, from a pragmatic standpoint, despite having few rigorously designed nutritional intervention trials in acute care patients, there remain several reasons to support the current approach of systematically screening inpatients for malnutrition and commencing nutritional therapy in those identified.…”
Section: Nutritional Therapysupporting
confidence: 62%
“…These associations tempt us to believe that improvement in nutritional status by the use of nutritional interventions also leads to improvements in patient outcomes. However, similar findings have been reported for nutritional factors, such as vitamin D, where associations suggested harmful effects, but intervention research failed to find benefit [ 15 , 16 ]. Still, from a pragmatic standpoint, despite having few rigorously designed nutritional intervention trials in acute care patients, there remain several reasons to support the current approach of systematically screening inpatients for malnutrition and commencing nutritional therapy in those identified.…”
Section: Nutritional Therapysupporting
confidence: 62%
“…Earlier studies suggested an association between vitamin D and certain conditions associated with increased resource use, such as chronic conditions, falls [ 1 ], frailty [ 30 , 31 ], and fractures [ 32 , 33 ]. Prior studies have suggested that vitamin D deficiency is associated with increased risk of hospital re-admission, nursing home admission, and increased hospital LOS [ 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Results from a recent review by Grädel et al [10] showed that high-quality evidence from interventional trials on the benefits of vitamin D supplementation in inpatients is currently lacking. The authors concluded that vitamin D screening and supplementation for the medical inpatient population in an acute care setting cannot be recommended based on current available evidence.…”
Section: Discussionmentioning
confidence: 99%